2022
DOI: 10.1136/fmch-2021-001430
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy and related factors among primary healthcare workers in a district of Istanbul: a cross-sectional study from Turkey

Abstract: ObjectivesThis study aimed to determine the COVID-19 risk perceptions, vaccination intentions and predictive factors of family physicians and family healthcare staff working in primary care in Üsküdar.DesignA cross-sectional study was performed using an online questionnaire to determine the demographic and general characteristics of the participants and their willingness to be vaccinated.SettingAn online questionnaire was applied to family physicians and family health workers working in primary care family hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 32 publications
2
28
0
1
Order By: Relevance
“…A total of 56 articles were included in the final sample consisting of cross-sectional studies (n = 48), cohort studies (n = 2), systematic reviews (n = 2), scoping reviews (n = 2), systematic review and meta-analysis (n = 1), and a grey literature report [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 56 articles were included in the final sample consisting of cross-sectional studies (n = 48), cohort studies (n = 2), systematic reviews (n = 2), scoping reviews (n = 2), systematic review and meta-analysis (n = 1), and a grey literature report [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60...…”
Section: Resultsmentioning
confidence: 99%
“…The cross-sectional and cohort studies were from Greece (n = 6), China (n = 5), France (n = 4), Turkey (n = 4), Italy (n = 4), Cyprus (n = 3), UK (n = 3), Germany (n = 2), Lebanon (n = 2), Spain (n = 2), Egypt (n = 2), the US (n = 2), Azerbaijan, Albania, Czech Republic, India, Iraq, Israel, Kosovo, Palestine, Saudi Arabia, Singapore, Slovakia, Switzerland, Tunisia, and the UAE ( Table 1 ) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , ...…”
Section: Resultsmentioning
confidence: 99%
“…This result could be due to the reported high rates of COVID-19-related morbidity and mortality among male COVID-19 patients. Similarly, another study in Turkey showed that the acceptance rates were higher in men [ 31 ]. Contrary to our study, COVID-19 vaccine acceptance was found to increase with the increase of age [ 28 ].…”
Section: Discussionmentioning
confidence: 95%
“…Different rates have been reported across the HCWs in Turkey. İkiışık et al [27] reported that the vaccine hesitancy rate was 29.0%, and 20.7% of respondents refused the COVID-19 vaccine in a "district of Istanbul city". Kaya et al [28] found that 48.8% of surveyed midwives had vaccine hesitancy, and 10.5% declared that they disliked getting vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the vaccination hesitancy was higher among women than men. İkiışık et al [27] showed that male doctors had a higher acceptance rate than females. Yilmaz et al [31] briefly reported that fear and lack of confidence were the most cited reasons related to vaccine hesitancy among HCWs.…”
Section: Discussionmentioning
confidence: 99%